Dampak Perubahan Iklim di Pasifik Selatan: Ancaman Naiknya Permukaan Air Laut Terhadap Eksistensi Negara dan Penduduk Kiribati - Melpayanty Sinaga; Yusril Yusril (Cenderawasih University, 2021)
Climate change is a complex and globalizing environmental issue that occurs almost all over the world, including the South Pacific islands. This article aims to examine the impacts of climate change on the Pacific community, marked by a sea-level rise that threatens the existence of the country and its population – particularly the Republic of Kiribati. This study also investigates the role of the Kiribati government in planning future strategies in response to the threat of rising sea levels. By using descriptive qualitative analysis, it found that Kiribati became one of the countries in the South Pacific whose existence and inhabitants would be threatened by the sea level rise in the near future. The impacts felt by the people of Kiribati thus far included storm surges, typhoons, floods, sea-level rise, seawater intrusion, and drought. However, the sea-level rise became the most experienced phenomenon by households in Kiribati. The Kiribati government has developed three strategies: adaptation, mitigation, and relocation. Adaptation and mitigation are identified as priorities while considering relocation as the last option.KEYWORDSClimate Change; Kiribati; Pacific; Sea Level Rise